The Comprehensive Modeling of Informational Coordination in Supply Chain of Automotive Industry by Meta-synthesis Method - Ali Mohaghar; Ahmad Jafarnejad; Mohamad Modares yazdi; Mohammad Reza Sadeghi Moghadam (Journal of Information Technology Management)
Regarding the extended concept of coordination generally orspecially in supply chain contexts, we aimed to identify the coordinationphenomenon in this research by determination of its elements anddimensions. The results of the previous researches, were analyzed by theMetha-synthesis research method and when seven steps were passed, thesupply chain coordination in automotive industry, were categorized in 5dimensions, 16 sub-dimensions and 57 elements. Finally, by using theShanon entropy method, the effect coefficient of the elements wasdetermined in 194 previous researches.